2018
DOI: 10.1002/cae.22053
|View full text |Cite
|
Sign up to set email alerts
|

A web‐based virtual laboratory for SHRIMP

Abstract: This paper introduces a novel web‐based virtual laboratory to assist teaching of Sensitive High Resolution Ion Micro‐probe (SHRIMP) implementation, called SHRIMP VL. This virtual laboratory is especially designed to aid learning of the instrument operation procedure. SHRIMP VL was developed based on hypertext preprocessor (PHP) technology and the Browser/Server application model, combined with the Yii framework and database technology. The virtual lab includes a virtual experiment platform to simulate the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…This virtual practicum is one alternative model in overcoming the problem of practicum implementation in schools, which sometimes requires a lot of time and expensive costs. Liu et al (2018) revealed that to modify a complete practicum can be done with a virtual form, especially for abstract physics concepts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This virtual practicum is one alternative model in overcoming the problem of practicum implementation in schools, which sometimes requires a lot of time and expensive costs. Liu et al (2018) revealed that to modify a complete practicum can be done with a virtual form, especially for abstract physics concepts.…”
Section: Discussionmentioning
confidence: 99%
“…The media will overcome the absence of laboratory activities that lead misconceptions by visualizing the concept (Saragih & Utami, 2019). The use of instructional media can improve learning efficiency, facilitate students in understanding concept be more concrete (Liu, He, Tian, Fan, & Yao, 2018) and clarify the presentation of messages and information served by teachers (Dewi & Mukminan, 2016) and improve the process and learning outcomes. The use of instructional media should be a concerning part for the teacher in every teaching and learning process (Dosi & Budingsih, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many authors emphasize the importance of virtual laboratories for training engineering specialists. Computer simulations have been increasingly more accessible for teaching and learning in various areas of physics and electronics . Interactive virtual laboratories are globally used in a wide range of educational establishments and are often a key subject of international conferences and research projects .…”
Section: Introductionmentioning
confidence: 99%
“…Virtual laboratories can significantly change the teaching mode and, as a result, reduce expenses on equipment, overcome time and space limitations and lack of experimental resources. Currently, a sufficiently large number of virtual engineering laboratories in various fields of physics and electronics have been developed [2,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, distance learning which requires laboratory workshops to be carried out remotely has gained a lot of popularity in higher education [5][6][7][12][13][14][15]. In this respect, the use of traditional hands-on laboratories is becoming impossible.…”
Section: Introductionmentioning
confidence: 99%